Privacy and Security: Answering the Wrong Questions Is No Answer. - Spafford, Eugene H. (Communications of the ACM, 2009)
In this article the author discusses efforts to build trustworthy computing systems. Attempting to make a computing system secure against all threats is not a realistic goal, the author suggests. Other topics include operating systems with flaws and weak controls adopted due to low cost and convenience and the importance of properly defining a problem related to cyber security and privacy.